PENERAPAN STRATEGI PEMBELAJARAN SAVI MENGGUNAKAN MEDIA EDUCATION CARD UNTUK MENINGKATKAN PEMAHAMAN KONSEP FISIKA SISWA KELAS VIII SMP NEGERI 23 PEKANBARU - Hafsi, Febzira; Ma?aruf, Zuhdi; Azizahwati, Azizahwati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research aimed to describe the understanding of physical concepts by the implementation of SAVI strategies (Somatic, Audiotory, Visual, and Intellectual) using media education cards and knowing differences student’s understanding of physical concepts by SAVI learning strategies using media education cards with conventional learning models. The research method used is Posstest-Only design. The research subjects were students of class VIII SMP Negeri 23 Pekanbaru, which is class VIIIA was an experimental class and class VIIID was a control class. The experimental class uses the SAVI learning strategy using education cards media and a control class with conventional learning. The data was obtained from concept understanding test which given to student after the learning process was carried out. Data were analyzed descriptively by using indicator of concept understanding criteria to provide an overview of students' understanding of concepts and also inferentially using the independent-sample t-test.The research result obtained were the average of students concept understanding score in the experimental class higher than controll class.Thus it was concluded that the implementation of the SAVI learning strategy using an education card media has given good influence, improved interest in learning, make students more active, So that it can increase student’s understanding concept of physics in SMP N 23 Pekanbaru on the material vibrations, waves, and sounds.Key Word : Concept Understanding, SAVI Learning Strategies, Education Card